2015
DOI: 10.1039/c4ay02787f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a restricted access material–macroporous hybrid monolithic column – for on-line solid-phase extraction of the sulfonamides residues from honey

Abstract: A novel RAM–HMC with superior enrichment and clean-up efficiency was prepared by an in situ method in a stainless-steel column, and used as a pre-column for on-line solid-phase extraction of sulfonamides residues from honey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Initially, the RAM‐HMC was prepared according to our previous work . The results of this research found that single organosilane (MTMS) was significantly different from mixed silanes (MTMS and tetramethoxysilane).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the RAM‐HMC was prepared according to our previous work . The results of this research found that single organosilane (MTMS) was significantly different from mixed silanes (MTMS and tetramethoxysilane).…”
Section: Resultsmentioning
confidence: 99%
“…The column has low column pressure and high mass transfer efficiency owing to unique pore structure . With the advantages of facile preparation, abundant surface functional groups, and controlled pore sizes distribution, the monolithic columns have been numerous reports such as organic polymer‐based, silica‐based and organic‐silica hybrid monolithic columns . Compard to the former monoliths, the hybrid monolithic column combines the merits of the former two monoliths and overcomes the inherent drawbacks like the instability under extreme pH and harsh solvents .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, polymeric monolithic columns with different polarities and functional groups can be fabricated by varying their chemical composition and configuration according to the analysis requirements. Because of these advantages, several polymer-based monolithic columns have been successfully used for the on-line pretreatment of compounds from environmental, food, and biological matrixes [21][22][23][24][25][26][27][28][29][30][31], e.g., ion-exchange sorbents [22], reversed-phase monoliths [24], restricted access monoliths [26], molecularly imprinted polymers [27], and hydrophilic sorbents [30]. The polyfunctional monolith monomers will dictate the extraction performance of the target analytes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve the determination of trace SAs, various sample preparation methods have been developed in various matrices, such as QuEChERS (quick, easy, cheap, effective, rugged and safe) method in animal tissues combined with highperformance liquid chromatography-Orbitrap (HPLC-Orbitrap) (Abdallah et al, 2014), solid-phase extraction method in water sample combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) (Zhou et al, 2012), microwave-assisted extraction method in sediments and soils combined with LC-MS/MS (Balakrishnanvimal et al, 2014) and on-line solid-phase extraction in honey combined with LC-MS/MS (Lv et al, 2015). However, these protocols usually need multi-step processing and have been proven to be time-consuming.…”
Section: Introductionmentioning
confidence: 99%